The Effect of Maternal Education and Antenatal Care on Basic Immunization Completeness in Children aged 12-23 Months in Asian and African: Meta-Analysis - Farida, Farida; Widyaningsih, Vitri; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Immunization is a process that makes a person immune or immune to infec